Nutrient-rich feed supplementation accelerates recovery of body condition and increases calf birth weight in Bali cattle affected by foot and mouth disease. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to evaluate the effects of feed supplementation on the body condition of cows suffering from foot and mouth disease (FMD) and the birth weight of their calves. Materials and Methods: The study involved 30 pregnant cows (6–7 months gestation), divided into five groups of six cows each. Groups A, B, C, D, and group E were supplemented with concentrates at levels of 0%, 0.2%, 0.4%, 0.6%, and 0.8% of body weight, respectively. The concentrates comprised cassava peels (60%), corn mill (40%), urea (3% of total feed needed), and minerals (25% of total feed needed). Variables: Following the onset of FMD symptoms, observations were made on the duration of hypersalivation, nasal discharge, snout and nose erosion, tongue and lip erosion, foot swelling, refusal to eat, and return to normal feed consumption. Results: The results showed that feed supplementation accelerated recovery such as time from hypersalivation, nasal discharge, muzzle erosion, and tongue (p < 0.05). However, no significant difference in interdigital wounds and duration of reluctance to eat due to FMD. Providing nutrient-rich feed also increases the body condition scores after FMD infection and the calf birth weight (p < 0.05) of Bali cattle. Conclusion: It was concluded that nutrient-rich feed supplementation accelerates cow recovery from FMD, maintains body condition, and increases the calf birth weight of Bali cattle.J. Adv. Vet. Anim. Res., 12(1): 106–116, March 2025http://doi.org/10.5455/javar.2025.l877